Howard Kazanjian a producer's life - Rinzler, J. W. 1962-2021 (Cameron + Company, 2021)
"A chronicle of the life and career of legendary movie producer Howard Kazanjian, who worked with directors ranging from Sam Peckinpah and Alfred Hitchcock to George Lucas and Steven Spielberg"--
from Hitchcock and Peckinpah to Spielberg and Lucas: 50 years of collaboration [Cover]
Keywords: Kazanjian, Howard -- 1942-; Kazanjian, Howard; Motion picture producers and directors / United States / Biography; Motion picture producers and directors; United States; Biographies; Biografie